2000
DOI: 10.2214/ajr.175.6.1751721
|View full text |Cite
|
Sign up to set email alerts
|

Sonography and MR Imaging of Bifid Median Nerve with Anatomic and Histologic Correlation

Abstract: Sonography and MR imaging can allow effective diagnosis and delineation of a bifid median nerve in the wrist. This diagnosis is important to make before carpal tunnel release or other wrist surgeries are performed to avoid nerve injury. Furthermore, the sonographic size criteria for diagnosing carpal tunnel syndrome in nonbifid median nerves may not be accurate in evaluating bifid median nerves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
58
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 10 publications
(18 reference statements)
1
58
0
3
Order By: Relevance
“…7,8,11,26) Anatomical variants such as persistent median artery or bifid median nerve may also be recognized. 16,28) Approximately 10% of patients have vascular anomalies, such as persistent median artery of the forearm, which runs parallel to the median nerve. 9) These anatomical variations are important to recognize, especially in the preoperative setting, because they may influence the way of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,11,26) Anatomical variants such as persistent median artery or bifid median nerve may also be recognized. 16,28) Approximately 10% of patients have vascular anomalies, such as persistent median artery of the forearm, which runs parallel to the median nerve. 9) These anatomical variations are important to recognize, especially in the preoperative setting, because they may influence the way of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, sonography has been evaluated for the evaluation of patients with CTS, 3,11,[16][17][18][19]21,25,28,31,32,34,35,37) and may be a useful alternative to the nerve conduction study, 7,11,20,21,23,31,34,38) with high sensitivity and specificity. 3,11,25,31,32,34,37) Most studies used nerve conduction as the gold standard.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Detection of median nerve anomalies with ultrasonography and MRI, showing 2 nerve trunks in the carpal tunnel, has been reported recently. 23,24 The increasing spatial resolution with the use of a 7-to 15-MHz broadband linear array transducer and the newly developed SonoCT technology leads to better delineation of the perineurium, fascicles, and septal structures within the nerve. This enables the examiner to differentiate high division proximally to the carpal ligament, with complete separation of fascicles and the perineurium, from a mere fascicle regrouping separated by septal structures but enveloped by a common perineurium.…”
Section: Discussionmentioning
confidence: 99%
“…1 In previous studies, BMN was reported to be associated with CTS due to its relatively higher cross sectional area (CSA) compared to a non-BMN which may lead compression in carpal tunnel. 1,[11][12][13] However, in a more recent study Granata et al, 14 reported similar frequencies of BMN in patients with CTS and the healthy control group. Hence, we aimed to determine the BMN frequency in patients with CTS and healthy control group, and to investigate the aforementioned association between CTS and BMN in our population.…”
mentioning
confidence: 87%